Diagnóstico legal de los procedimientos de actuación y el nivel de accidentabilidad para el diseño y estandarización de los procesos operacionales seguros en el cuerpo de bomberos de Ambato en el año 2015 - Andrade Clavijo, Byron Patricio (2017)
This research work is based on the diagnosis of operational procedures and its impact on the level of accident rate that can be generated in the operational staff of the Fire Department of Ambato. It begins with the study of existing procedures of administrative and operative types. One proceeds to identify the condition of the equipment and vehicles that are used habitually to know the risk of accident. To complement the study one proceeds to determine proactive indicators of accident rate and to evaluate the risks by the triple criterion method NTP 330. The hypothesis that is tested in this work is: ¿The design and standardization of the action procedures, will allow to reduce the level of accident rate in the Municipal Company Ambato´s Fire Department? The result determines that it is necessary to carry out the action procedures, the proposed plan establishes all the standards and protocols that must be developed to avoid accidents.